A Decision-Making Model for Community-Based Food Industry to Support Poverty Alleviation in East Indonesia: Case Study of East Sumba Regency - Ratih Dyah Kusumastuti; Fanny Martdianty; Rifelly Dewi Astuti; Nurmala Nurmala (Department of Management, Faculty of Economics and Business, Brawijaya University, 2016)
Provinces in the eastern part of Indonesia still have high percentage of residents living below the poverty line. However, some provinces are the producers of food commodities. The One Village One Product (OVOP) movement has been proven to be able to reduce the poverty level and can be implemented in East Indonesia, especially by developing the community-based food industry. The objective of the research is to develop a decision making model to determine the best suitable community-based food industry to be developed optimally in East Indonesia using Analytic Hierarchy Process (AHP). We identify five criteria for the model from the literature and interviews with experts, namely resources, demand, supporting industries, strategy and competitiveness, and supports from government and other parties. We apply the model for the case of East Sumba regency of the East Nusa Tenggara (NTT) province, to select from alternatives, namely cassava, banana, corn and peanut-based food industries. The results show that banana-based industry is chosen as the best-suitable community-based food industry, mainly due to the uniqueness of the banana-based product and high production of banana in the area.